41 Circulating levels and prognostic cut-offs of sST2, high-sensitivity troponin T, and NT-proBNP in women vs. men with chronic heart failure. (8th December 2021) - Gentile, Francesco; Aimo, Alberto; Jannuzzi, James Lj; Richards, Mark; Lam, Carolyn Sp; Boer, Rudolf A. De; Meems, Laura Mg; Latini, Roberto; Staszewsky, Lidia; Anand, Inder S.; Cohn, Jay N.; Ueland, Thor; et al.
Abstract: Aims: Limited evidence exists on sex-related differences in clinical value of biomarkers in chronic heart failure (HF). We aimed to define plasma levels, determinants, and optimal prognostic cut-offs of soluble suppression of tumourigenesis-2 (sST2), high-sensitivity troponin T (hs-TnT), and N-terminal pro-B-type natriuretic peptide (NT-proBNP) in female and male chronic HF patients. Methods and results: Individual data of patients from the BIOS (Biomarkers In Heart Failure Outpatient Study) Consortium with sST2, hs-TnT, and NT-proBNP measured were analysed. The primary endpoint was a composite of 1-year cardiovascular death and HF hospitalization. The secondary endpoints were 5-year cardiovascular and all-cause death. The cohort included 4540 patients (age: 67 ± 12 years, LVEF 33 ± 13%, 1111 women, 25%). Women showed lower sST2 (24 vs. 27 ng/ml, P  < 0.001) and hs-TnT level (15 vs. 20 ng/l, P  < 0.001), and similar concentrations of NT-proBNP (1540 vs. 1505 ng/l, P  = 0.408). Although the three biomarkers were confirmed as independent predictors of outcome in both sexes, the optimal prognostic cut-off was lower in women for sST2 (28 vs. 31 ng/ml) and hs-TnT (22 vs. 25 ng/l), while NT-proBNP cut-off was higher in women (2339 ng/l vs. 2145 ng/l). The use of sex-specific cut-offs improved risk prediction compared to the use of previously standardized prognostic cut-offs (Figure). Conclusions: In patients with chronic HF, levels of sST2 and hs-TnT, but not of NT-proBNP are lower in women. Lower sST2 and hs-TnT and higher NT-proBNP cut-offs for risk stratification could be used in women.